Como o Mundo Mudou as Mídias Sociais - Miller, Daniel; Costa, Elisabetta; Haynes, Nell; McDonald, Tom; Nicolescu, Razvan; Sinanan, Jolynna; Spyer, Juliano; Venkatraman, Shiram; Wang, Xinyuan (Why We Post, 2019)
How the World Has Changed Social Media is the first book by Why We Post, a book series that investigates the findings of nine anthropologists who have spent 15 months living in communities in different parts of the world, including Brazil, Chile, China, England, India, Italy, Trinidad and Turkey. This book offers a comparative analysis that summarizes research findings and analysis of the impact of social media on politics and gender, education, and commerce. What is the result of the increased emphasis on visual communication? Are we becoming more individualistic or more social? Why is public social media so conservative? Why can't equality on the internet nullify inequality? How did memes become the moral police of the internet?